Fragmentarisation of the Vlach settlement in the Olympus and Vermio areas at the turn of 19th and 20th centuries - Paszkiewicz, Jędrzej (Balcanica Posnaniensia. Acta et studia, 2022)
The aim of the article is to describe, on the basis of historiography, the evolution of main Vlach settlements located in the Olympus and Vermio regions. All they were created as the results of migrations of the population from the Pindos area at the turn of the 18th and 19th century. The culmination of these movements fell on the second part of the 18th (Olympus) and the first part of the 19th century (Vermio). During the following decades the Vlach enclaves, such as Livadi, Kato Vermio or Xirolivado experienced a gradual fragmentarisation. Although the part of the population continued traditional forms of economic activity and kept in contact with its „native” settlements from the Pindos area, the majority became assimilated with the local Greek population. Vlachs supplied Greek-speaking communities in Veroia, Naoussa, Katerini, abandoned the transhumant economy, traditional dialects and migrated to Romania.